ChemInform Abstract: Synthesis of Novel Fluorinated 11H‐Azaindolo[3, 2‐c]isoquinolines. Issue 45 (14th October 2013) - Atmakur, Krishnaiah; Emmadi, Narender Reddy; Balasubramanian, Sridhar
Abstract Attempts to cyclize pyrrolo[2, 3‐b]pyridins (II) via Pictet‐Spengler reaction failed.